The Road to an Academic Medicine Career: A National Cohort Study of Male And Female U.S. Medical Graduates - Andriole, Dorothy A. (2012)
PURPOSE: To explore the relationship between gender and full-time faculty appointment in a national cohort of contemporary U.S. medical school graduates. METHOD: The authors analyzed de-identified, individual records for the 1998–2004 national cohort of U.S. medical graduates using multivariate logistic regression to identify predictors of full-time faculty appointment through July 2009. They reported adjusted odds ratios (aOR) significant at P <.05. RESULTS: Of 66,889 graduates, 12,038 (18.0%) had held full-time faculty appointments. Among all graduates, women (aOR = 1.21) were more likely than men to have held faculty appointments. Among male, but not female, graduates, those who participated in research during college (aOR = 1.08), entered medical school with greater planned extent of career involvement in research (aOR = 1.08), and authored/coauthored a research paper during medical school (aOR = 1.12) were more likely and those with higher debt were less likely (aOR = 0.96) to have held faculty appointments. Among only faculty appointees, higher proportions of men than women had participated in medical school research electives (63.5% [3,899/6,138] vs. 54.2% [3,197/5,900]; P <.001) and authored/coauthored research papers during medical school (44.1% [2,707/6,138] vs. 33.6% [1,981/5,900]; P <.001); female faculty had reported higher debt at medical school graduation than had male faculty (P = .014). CONCLUSIONS: In this national cohort of U.S. medical graduates, women were more likely than men to have held full-time faculty appointments. However, male and female faculty appointees entered academic medicine with different research experiences and debt, possibly impacting their academic medicine career trajectories.